Bioadministration: A Concept for Analyzing Human and Non-Human Organism Interaction in Organizational Studies within the Context of Longevity - Fonseca, Vasco; Zózimo, Ricardo; Monteiro, Maria Helena (Journal of Ecohumanism, 2024)
Embark on a thought-provoking exploration with us as we delve into the fascinating world of bio-administration—a convergence point where the intricacies of biology intersect with the dynamics of organizational management. Authored by an interdisciplinary team comprising the vision of an oncologist, on guidance of an economics professor and a public administration professor, this article sheds light on the emerging concept of bio-administration and its implications for organizational theory and practice. From the fundamental workings of life to the complex structures of human society, join us on this insightful journey as we uncover the synergies between biology and organizational dynamics.